(untitled) (Revista Nacional de Odontología, 2020)
Introduction: Pediatric dental traumas are common events before 3 years old. Among common consequences in permanent teeth successors are structural anomalies, crown or roots morphologic anomalies, eruption anomalies and impacted teeth. Whatever the type of trauma may be, monitoring is important. Case report: This paper reports a case of dental-alveolar trauma in a 9-month-old boy, who fell down in a pair of stairs. The traumatic area included: right temporary central lower incisor with lateral luxation, mobile and the gum surrounding displacement; left temporary central lower incisor with one grade of mobility. After the clinical and radiological diagnosis, the decision is to extract the right temporary central lower incisor. Patient did not come again to de control appointment until he was around 7-year, 7 months-old. The eruption of the right permanent central lower incisor occurred, which presented crown dilaceration and enamel hypoplasia. The left permanent central lower incisor with enamel hypoplasia. Multidisciplinary appointments were made to decide actions to take with the permanent teeth as a result of trauma to the temporary teeth. Conclusion: Temporary dental trauma at an early age can produce consequences to the permanent successor. It is important to inform parents in order to make easy the evaluation and the opportune dental procedures.